The Effect of Mind Mapping on Jamboard in Tenth-Grade Students Past Tense Mastery - Badriyah, Desy Qomariyatil; Devanti, Yeni Mardiyana; Laeli, Anita Fatimatul (International Journal of English Education and Linguistics (IJoEEL), 2024)
The purpose of this study to investigates the impact of mind mapping in google Jamboard on students' Simple past tense mastery. The instrument used in this research is a multiple-choice test. Quasi-experimental design is a method in this research with a sample of 60 class X MA Darullughah Wal Karomah students who were divided into control and experimental groups. The experimental group received teaching using mind mapping on google Jamboard, while the control group followed traditional teaching methods. The data shows that the average value obtained in the experimental class was 73.07, while in the control class it was 64.69. The research results show that the use of mind mapping in google Jamboard can improve students' simple past tense mastery. Mind mapping is an effective way or method for teaching grammar. Additionally, combining mind mapping with a digital platform like google Jamboard can create a more interactive, fun, and engaging learning environment. research should explore the impact of mind mapping through jamboard on other areas or skills of language learning. This study did not have much time. If the time were longer enough, the finding would be more effective. So, in the future, researchers should have more time to do it and ensure the internet connection is good because if it is bad, it will also take a lot of time